Characteristics of leakage current during surface discharge at the oil-pressboard interface - Zainuddin, Hidayat; Lewin, P.L.; Mitchinson, P.M. (2012)
Surface discharge at the oil-pressboard interface leads to the development of a conducting path that is generally accepted as white marks due to localized heating. The visible white marks are believed to be due to partial discharge (PD) energy that is high enough to dry out the pressboard through vaporizing the moisture and breaking oil molecules to generate gases in the pressboard pores. A long period of electrical stress applied to a surface discharge experiment using a needle-bar electrode configuration has led to the formation of full-gap white marks on the pressboard surface that bridged the needle tip and earth bar. During the surface discharge, leakage current may occur intermittently that sometimes is visible in the form of full discharge of arcing at the oil-pressboard interface bridging the needle tip and earth bar. This condition is expected to be similar to that of dry-band arcing from inclined-plane tracking experiments for outdoor insulation. This paper explains the surface discharge experiment and details the obtained leakage current characteristics in terms of waveforms and frequency spectra. Correlation between leakage current measurements using a shunt resistor and PD signal detection has been undertaken in order to identify the useful information for condition monitoring of surface discharge in a large transformer. An equivalent circuit to represent the leakage current occurrence at the oil-pressboard interface without considering the superimposed pulses due to individual PD events is also proposed. The effect of moisture on the experimental results is also discussed.